Roots Program in Preventing Bullying and Improving the Character of Junior High School Students - Agung, Ida Bagus Agung Mahayana (Universitas Pendidikan Ganesha, 2025)
Bullying in school environments remains a significant issue in Indonesia, affecting students’ psychological well-being and the overall educational climate. This study aims to evaluate the effectiveness of the ROOTS Program in preventing bullying and enhancing the character development of junior high school students. The research employed the CIPP evaluation model (Context, Input, Process, Product) using a quantitative approach. The study population consisted of 85 respondents, including 76 students and 9 teachers. Data were collected through questionnaires, interviews, and documentation, and were analyzed descriptively using T-score analysis techniques. Based on T-score analysis of the four variables (Context, Input, Process, and Product), the results indicate the overall effectiveness of the program. The Context variable produced 61 positive scores (+) and 24 negative (-), indicating that the program’s implementation context was highly effective in creating a safe and inclusive environment. The Input variable recorded 46 positive scores (+) and 39 negative (-), showing that the program's inputs were generally good, although improvements are needed in terms of resources and educator training. The Process variable obtained 66 positive scores (+) and 19 negative (-), suggesting the program’s implementation process was effective. The Product variable recorded 57 positive scores (+) and 28 negative (-), indicating positive outcomes in reducing bullying cases. It can be concluded that the ROOTS Program is effective in building an empathetic, inclusive, and bullying-free school culture at the junior high school level. The evaluation recommends strengthening teacher training and resource support to ensure the sustainability of the program.